Mitochondria and Antioxidant Targeted Therapeutic Strategies for Alzheimer's Disease - Dumont, Magali (2010)
Oxidative stress and mitochondrial dysfunction are important features present in Alzheimer's disease (AD). They appear early and contribute to disease progression, both in human postmortem AD brains as well as in transgenic AD mouse brains. For this reason, targeting oxidative stress and mitochondria in AD may lead to the development of promising therapeutic strategies. Several exogenous antioxidant compounds have been tested and found beneficial in transgenic AD mice, such as vitamins and spices. However, their efficacy was much more modest in human trials. More recently, new strategies have been elaborated to promote endogenous antioxidant systems. Different pathways involved in oxidative stress response have been identified. Compounds able to upregulate these pathways are being generated and tested in animal models of AD and in human patients. Upregulation of antioxidant gene expression was beneficial in mice, giving hope for future avenues in the treatment of AD and other neurodegenerative disorders.